Improving Income through Farmers’ Group Empowerment Strategy - Desiana, Nia; Aprianingsih, Atik (School of Business and Management Institut Teknologi Bandung, 2017)
Abstract: During recent years the concept of farmer empowerment has been put on the agenda and now is a part of Indonesian’s government program. Empowerment of farmers’ group considered necessary because, in agricultural development, farmers’ group are the key development resource and subject in developing their agricultural efforts. This paper aims to explore the farmer’s group empowerment strategies to improve their income. The paper is based solely on the reviews of literature on the topic of farmer’s group and empowerment to explore the phenomena in the agricultural sector. Based on the findings, the paper proposes the farmers’ group empowerment strategies such as farmer’s group learning and innovation and information and communication technology (ICT) have a positive influence on improving their income.Keywords: Empowerment, farmers group, income, strategy, agriculture, learning, innovation, ICT